Smart Power Distribution Box with Power and Fault Monitoring using IoT - Mohd Shuhaimi, Anis Mustaqim; Kamarudin , Muhammad Saufi (Evolution in Electrical and Electronic Engineering, 2024)
This paper describes the design, development, and deployment of a smart distribution box enabled by the Internet of Things (IoT) with the goal of improving defect detection, power monitoring, and overall energy management in single-phase residential power applications. The PZEM-004T100A module for measuring electrical parameters and the ZMPT101B voltage sensor for monitoring voltage levels are two examples of the advanced sensor technologies integrated into the project. This allows for comprehensive and real-time monitoring of electrical parameters like voltage, current, power consumption, and temperature. The Blynk platform allows the smart distribution box to be connected to smartphones, making it easy to use and accessible for users. With the use of this connectivity, customers may improve their energy management practices by having remote access to vital power usage data, receiving defect warnings instantly, and estimating bills accurately. Intelligent monitoring capabilities, precise problem detection, and user-friendly interfaces for web and smartphone applications that guarantee a smooth user experience are some of the system’s key characteristics. The system’s ability to dramatically improve energy management, increase safety, and decrease downtime in residential settings is highlighted by the thorough real-time data analysis and the precision of the fault detection techniques used to illustrate the system’s effectiveness. This research demonstrates how smart technology may revolutionize power distribution networks by tackling typical problems including excessive power use, distribution board failures, and customer misunderstanding about energy consumption. According to the report’s conclusion, the smart distribution box provides a full answer for contemporary energy management problems in residential applications thanks to its integrated IoT capabilities and cutting-edge sensor technologies.